Digital Transformation in Religious Organizations: The Application of Data Management for Church in Magelang - Fibriani, Charitas; Kristiyani, Dian Novita; Susetyo, Yeremia Alfa; Yulia, Hanita (Jurnal Abdimas, 2024)
The Plengkung Javanese Christian Church Synod (GKJP) is one of the Protestant church groups located in several areas on the island of Java. The condition of data recording in GKJP is still done by recording using book media. This causes data inconsistency or redundancy. GKJP also requires data management that can be used to obtain classes for congregation groups according to several needs. This Community Service aims to build the GKJP Magelang City Congregation Information System, where this system will focus on recording congregation data so that it is hoped that the problems of inconsistency and redundancy can be resolved and can utilize the congregation data to obtain certain criteria groups using the classification analysis menu.